POTENSI KECAMATAN SALEM DALAM PENDAPATAN ASLI DAERAH - Caroline, . (Jurnal Ekonomi & Studi Pembangunan, 2010)
Several factors contribute significantly in implement regional autonomy is a good human resources, sources of local revenue, as well as the organization and good management. Salem subdistrict in this study is one of the region in Brebes district that has a lot of potential economic wealth, natural resources, and human resources that can be developed better to increase local revenues. This study used SWOT analysis and Subdistrict Alocation Funds (ADK). SWOT Analysis is used to compare between internal factor and external factor. Aftera thorough analysis, the results showed that Salem subdistrict is in third strategic position. It means the development of subdistrict needs to consider factors that influence both internally and externally and integrated. The program will be developed covering aspects: human resources, land use, economic, educational facilities, health facilities, electricity networks, telephone networks, drainage networks, water networks, and road network.